CRITERIA FOR MARKET SEGMENTATION FOR THE MARKET IN THE EU - Štrbac, Maja (Economics of Agriculture, 2010)
The primary goal of market segmentation is to target attractive market segments. The purpose for segmenting a market is to allow marketing program to focus on the subset of prospects that are "most likely" to purchase offering. Market segmentation can stimulate marketing and transform business to new levels of success. There are numerous ways to carry out a market segmentation for the fruit and vegetables market in the EU. These include dividing the market by geographic, demographic, or behavioural variables. Each has a strong influence on the consumption patterns of fruit and vegetables. They are not separate entities but overlap. Some main characteristics within each are described below.